2020
DOI: 10.3390/jcm9123877
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Microbial Profiles of Infected Root Canals in Traumatized Teeth

Abstract: Traumatic dental injuries in young individuals are often exposed to the invasion of oral microorganisms that leads to pulp necrosis. Infective necrosis in permanent teeth not-fully-developed causes aberrant root formation. Regeneration endodontic treatments (RETs) have shown promising results by promoting continued root development by stem cells. Critical to the success of RET is the thorough disinfection of the pulpal space. To establish effective antimicrobial protocols for root canal disinfection, the invad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…Our characterization and analysis of pre‐treatment microbiological samples, using NGS data, showed that a homogeneous and reproducible microbial community was obtained between the experimental groups (alpha diversity). Although our experimental biofilm model may not completely reproduce the flora of the root canal system—which can vary substantially between individuals, infection stages and types (primary and secondary/persistent) (Manoharan et al, 2020; Sassone et al, 2008; Siqueira & Rôças, 2009)—the model showed to be reproducible and composed of bacterial genera implicated in endodontic infections.…”
Section: Discussionmentioning
confidence: 93%
“…Our characterization and analysis of pre‐treatment microbiological samples, using NGS data, showed that a homogeneous and reproducible microbial community was obtained between the experimental groups (alpha diversity). Although our experimental biofilm model may not completely reproduce the flora of the root canal system—which can vary substantially between individuals, infection stages and types (primary and secondary/persistent) (Manoharan et al, 2020; Sassone et al, 2008; Siqueira & Rôças, 2009)—the model showed to be reproducible and composed of bacterial genera implicated in endodontic infections.…”
Section: Discussionmentioning
confidence: 93%
“…2016/520-31). Sample collection, processing, and characterization of isolates was performed as previously described ( Manoharan et al., 2020 ). Briefly, samples were collected from teeth isolated with a rubber dam and using strict aseptic techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Fusobacterium nucleatum and S. exigua were the most prevalent isolated species from young infected and traumatized teeth ( Manoharan et al., 2020 ), while E. faecalis and A. gerensceriae were chosen for their role in root canal treatment failure ( Siqueira and Rocas, 2008 ). Lactobacillus gasseri , which displayed probiotic traits, had been previously isolated from the oral cavity of healthy infants ( Vestman et al., 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fusobacterium nucleatum is a high-frequency specie isolated from the oral cavity but usually absent or very rarely detected elsewhere in the human body [11]. F. nucleatum is closely related to the development of periodontitis [12] and endodontic infections [13] and is described as a possible oncogene related to colorectal cancer, pancreatic cancer, and oral cancers [14]. This Gram-negative bacterial specie is able to adhere to a variety of oral microbes and can produce a group of virulence factors and toxic metabolites, including lipopolysaccharides, porins, butyrate, and propionate ammonia [15].…”
Section: Of 23mentioning
confidence: 99%
“…The bacterial isolates were obtained as previously described [13]. Briefly, the contents of the root canal were absorbed into sterile paper points and transferred to fluid thioglycolate medium supplemented with agar.…”
Section: Bacterial Strains Supernatants and Growth Conditionsmentioning
confidence: 99%